Biorational insecticides against the potato tuber moth (Lepidoptera: Gelechiidae) on stored potatoes - G. Saour; H. Ismail; I. Jassem; S. Tamer (Advances in Horticultural Science)
This study was conducted to evaluate the residual activity and efficacy of spinosad, emamectin benzoate, and chromafenozide on potato tuber moth, Phthorimaea operculella. Almost 0% egg hatch of 1-1.5 and 4-4.5-day-old eggs occurred when eggs were treated topically with spinosad at a concentration of 216 mg/L. No ovicidal activity was observed when emamectin benzoate and chromafenozide were tested against the eggs at concentrations of 5, 10, 15 and 37.5, 75 mg/L. Spinosad and emamectin benzoate were equally highly toxic to larvae (100% mortality) even when they were used at low rates. A relatively small proportion of F1 adults (≈11 to 20%) emerged in the chromafenozide treatment at concentrations of 37.5 and 75 mg/L. One hundred percent larval mortality was noted when potato tubers were sprayed with spinosad and emamectin benzoate and stored for at least 90 days after application. Whereas, chromafenozide applied at 75 mg/L was effective in reducing moth emergence, exhibiting activity for 14 days only after application; thereafter a similar number of F1 adults occurred in chromafenozide and control treatments. Thus, spinosad and emamectin benzoate could be used to efficiently protect potato tubers from P. operculella infestation for three months in unrefrigerated rustic potato stores.